Commercialization in agriculture in rural Viet Nam, 2006-14 - Andy McKay; Chiara Cazzuffi; Emilie Perge (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
The vast majority of households in rural Viet Nam undertake agricultural activities and for many this is their main livelihood. Moreover, this agriculture has become increasingly commercialized over time. This paper uses the five wave VARHS balanced panel data set to analyse three aspects of this commercialization: the likelihood of (1) selling rice (the dominant crop); (2) growing cash crops; and (3) engaging in aquaculture. A panel regression analysis identifies factors commonly associated with a more commercial orientation, with important factors including land size, the nature of cultivation, access to infrastructure, and receipt of credit.
Keywords: O13; Q12; Q22; 330; agriculture; commercialization; Vietnam; panel data